Discussion-Based Approach to English Language Teaching and Learning A Digital Dedicated Language Laboratory - Naima Hamlaoui; Nacereddine Benabdallah (My University, 2015)
One of the most fundamental concerns of teaching English as a foreign language (EFL) is to maximize the opportunities of learner-learner talk. Digitalized technological facilities can motivate committed teachers to adapt and adopt innovative ways of teaching oral skills. This article reports on an action research project implemented during one semester with a group of 14 willing Master students at the Department of Foreign Languages, Mohamed Cherif Messadia University, Souk-Ahras, Algeria. The aim was to investigate the effectiveness of the Digital Dedicated Language Laboratory (DDLL) in teaching English through a discussion-based approach. A well designed protocol made up of three types of discussion: framing, conceptual, and application discussions was adopted. The findings revealed that students were able to develop their linguistic, socio-cultural and pragmatic competences. They were also given the opportunity to exploit the various facilities, and tools available at the DDLL